1992
DOI: 10.1093/bja/68.4.381
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Text Entries Within a Manually Compiled Anaesthetic Record

Abstract: We have examined the accuracy of text entries within a manually compiled anaesthetic record by comparing the record of the anaesthetist with that of an observer, present throughout the procedure but whose sole purpose was the documentation of perioperative events. Eighty-six items of information were analysed for accuracy from 197 records. The mean proportion of omissions was 35% and the mean proportion of incorrect entries was 3.4%. Where no entry should have been made, the mean proportion of unwarranted entr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 22 publications
1
8
1
Order By: Relevance
“…A number of studies looking at handwritten records in isolation have shown completion rates that are generally lower than ours [16][17][18]39 . The relatively high completion rates for handwritten charts in our study may help to explain why we could not demonstrate a significant difference.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…A number of studies looking at handwritten records in isolation have shown completion rates that are generally lower than ours [16][17][18]39 . The relatively high completion rates for handwritten charts in our study may help to explain why we could not demonstrate a significant difference.…”
Section: Discussioncontrasting
confidence: 57%
“…There was no significant difference in the total score for completeness between electronic (78%) and handwritten (83%) records (P=0. 16). Handwritten records were more complete with respect to weight (P <0.0001), American Society of Anesthesiologists' physical status score (P <0.0001), the size and type of artificial airway used (P=0.003) and a record of the surgeons involved (P=0.0004).…”
mentioning
confidence: 97%
“…Anaesthetic records are traditionally compiled by hand, a process that accounts for about 15% of an anaesthetist’s intraoperative time 1516 Handwritten records are often incomplete and inaccurate,6 17 18 which might reduce or negate their value for any of the above purposes.…”
Section: Introductionmentioning
confidence: 99%
“…The accuracy of text entry data on anesthetic records has been assessed previously (also in a New Zealand hospital). 26 The findings suggest that text entry data generally have a high degree of accuracy and that the major deficiency in the quality of text entries is completeness.…”
Section: Discussionmentioning
confidence: 99%